The association of autonomy support on memory need satisfaction and goal progress - Chua, Sook Ning (2022)
Self-defining memories reflect our enduring concerns (past and present) and our desired future outcomes. One of the important characteristics of self-defining memories is need satisfaction, such that the higher level of satisfaction of the needs for autonomy, relatedness, and competence in memories positively predicts well-being and relationship satisfaction. Based on past research showing that autonomy supportive environments promote need satisfaction, we hypothesized that autonomy support would lead to greater goal-related need satisfying memories which would in turn promote goal progress. We conducted three prospective studies to test our hypothesis. Participants were asked to list a current goal, and to rate perceived autonomy support from a significant other and their goal progress. They were also asked to select and describe a significant memory related to the goal and rate the extent to which they felt competent, autonomous and related in the memory. We found that changes in need satisfaction in goal-related memories over time mediated the relationship between autonomy support and goal progress. This paper highlights how interpersonal support can influence self-regulation by shaping self-defining memories.